The Role of Marketing Research in the Field of Tourism - Mukhammadieva Nodira (American Journal of Economics and Business Management, 2023)
The article discusses the importance of marketing research in the field of tourism, It will consider the importance of marketing research in influencing the success of marketing operations and its relationship to influencing customers and its ability to influence their purchasing decision, and this is due to the ability of marketing research to collect information, study and track the tourism market, as well as study and understand the needs of tourists, and consider the role and importance of marketing research in the development and prosperity of the tourism industry.